Growth response of one-year-old 'Granny Smith' apple shoots in relation to time of pruning - Oosthuyse, S. A.(Steven Andrew) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1987.